Implementasi Model Pembelajaran Berbasis Project Based Learning (PJbL) untuk Meningkatkan Pemahaman Mahasiswa pada Mata Kuliah Psikolinguistik di Program Studi Pendidikan Bahasa Arab FKIP Universitas Jambi - Harianto, Neldi; Mu’id, Abdul; Vahlepi, Sahrizal (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to determine students' ability to write scientific articles in the Psycholinguistics Course using a Project Based Learning (PJbL) learning model. The method used in this research is classroom action research with a qualitative descriptive approach. The results found in the research were that the implementation of the PJbL learning model in the Psycholinguistics course showed good results, this was obtained from the students' average scores. The pre-test was 70 and the results of post-test 1 were 70.50 and the results of post-test 2 were 80.25. Apart from that, there is a tendency for student learning outcomes to increase. Thus, the implementation of the Project Based Learning (PJbL) learning model was successful in increasing students' understanding of the Psycholinguistics course in the Arabic Language Education Study Program.